410 Gone - Infocide in Open Content Communities - Reagle, Joseph (AoIR Selected Papers of Internet Research, 2012)
Infocide, the purposeful retraction and deletion of an online identity, is accompanied by a confusing set of neologisms such as cybersuicide and information suicide. I distinguish and identify these variations as a form of cyberlanguage. I then explore the complexities of infocide in open content communities (e.g., Python, Wikipedia, Ruby, Debian and Ubuntu) with respect to reasons, enactment, and community reactions. I find that infocides are often prompted by the exhaustion of maintaining an online life, by discontent towards an online community, and over privacy concerns that ones real and online identifies have intersected. While some infocide is concise and complete, infocide is occasionally graduated, such as when one removes aspects of one’s identity including advanced status and capabilities (e.g., as an administrator). Because of the temptation to return to one’s former identity, infocide is sometimes made irreversible, such as by changing one’s account password to a random string. An equally interesting aspect of infocide is a community’s reaction. I explore the responses of gratitude, sleuthing (attempting to identify more information, including motivation, about the exit), drama, and the preservation of contributions about the exit.